The World Bank's Support for Subnational Governance in Large Federal Countries : Lessons Learned from Argentina, Brazil and Nigeria - Stoykov, Petar Georgiev; Yilmaz, Serdar (World Bank, Washington, DC, 2022)
Limited local tax revenue and low public sector efficiency are two critical problems of public sector management and key constraints for the economic and social development of many subnational governments in large federal countries. To create fiscal space without compromising macroeconomic stability and fiscal sustainability, there is a need for reforms that lead to better use of public resources and improved expenditure efficiency through reforms in budgeting, procurement, and tax administration. This note presents lessons learned from the World Bank’s subnational governance projects in three large federal countries - Argentina, Brazil and Nigeria - between 2008-2017. These lessons learned can be useful in shaping the design of future subnational governance projects in other federal countries, particularly those projects seeking to improve service delivery, public expenditure systems and core governance institutions.